P09.26 Trends in gonorrhoea positivity by nucleic acid amplification testing versus culture in heterosexual men in victoria, australia, 2007–2014. (13th September 2015) - Mannion, PK; Fairley, CK; Fehler, G; Chen, MY; Bradshaw, CS; Chow, EPF
Abstract : Introduction: A three-fold increase in Neisseria gonorrhoeae (gonorrhoea) notifications was reported amongst low prevalence  women without a change in the proportion positive by culture, suggesting that screening for gonorrhoea by nucleic acid amplification test (NAAT) is not recommended in low prevalence populations due to low specificity of detection. This study aimed to identify whether there is a change in the rates of gonorrhoea positivity by culture in heterosexual men in Victoria, consistent with increased notifications. Methods: Three data sources from 2007 to 2014 were used: notification data from the Victorian Department of Health, Medicare Item numbers for single and duplex chlamydia NAATs, and the proportion of new patients attending Melbourne Sexual Health Centre (MSHC) with gonorrhoea diagnosed by culture. Multivariate logistic regression analyses were used to examine the association between gonorrhoea positivity and known risk factors. Results: Gonorrhoea notifications by NAAT in heterosexual men in Victoria increased from 38 in 2007 to 169 in 2014. There has been a five-fold increase in annual Medicare Items for chlamydia and a second NAAT, whilst only a modest increase in chlamydia only NAAT. A total of 28, 014 heterosexual men attended MSHC for first consultation between 2007 and 2014, and the overall gonorrhoea positivity by culture at MSHC was 0.93% (n = 260). No significant trend in annual gonorrhoea positivity (aOR 1.04, 95% CI: 0.97–1.10, p = 0 .270) was observed after adjusting for age, number of female sexual partners and condom use in the last three months, recent arrival in Australia, and previous sex overseas. Conclusion: These data suggest gonorrhoea positivity in heterosexual men is stable, despite increasing notification rates. An increase in false positive results due to low specificity of gonorrhoea NAAT may explain the observed trend. Disclosure of interest statement: This work was supported by the National Health and Medical Research Council (NHMRC) program grant APP1071269. No funding was received from pharmaceutical or biotechnology sectors.